Defining antigypsyism as part of the fight for Roma rights in the Slovak Republic - Havírová, Zuzana (Romano džaniben, 2025)
Antigypsyism is a specific form of racism that is perpetrated against Romani men and women in order to stigmatize, dehumanize and legitimize the violence that is perpetrated against them in various forms. Antigypsyism is based on historical forms of discrimination, prejudices and stereotypes. The structural form of antigypsyism has an impact on the successful integration of Romani men and women into society, reinforcing marginalisation. The article analyses structural forms of antigypsyism in its historical context and in state policies. At the same time it provides an insight into the development of a definition of antigypsyism in Slovakia which has become part of the Concept for combating radicalisation and extremism until 2024 and the Strategy for Roma equality, inclusion and participation until 2030. An important factor in the adoption of the definition in the national concept was the systematic work of the civil sector, which was influenced by European initiatives. The author of the article was part of the working group that developed the definition of antigypsyism.
Keywords: Antigypsyism; Roma; inclusion; non-profit sector; advocacy; participation